P Perdamaian Dunia di Era Globalisasi dalam Perspektif Metafisis Alfred North Whitehead: World Peace in the Era of Globalization in the Metaphysical Perspective of Alfred North Whitehead - Sihombing, Yusuf Mario; Riyanto, FX. Eko Armada (Undiksha, 2024)
The current global society is increasingly filled with various complex problems. War, the phenomenon of the